Do Lawyers Matter? Early Evidence on Eviction Patterns After the Rollout of Universal Access to Counsel in New York City. Issue 3 (3rd September 2021) - Ellen, Ingrid Gould; O'Regan, Katherine; House, Sophia; Brenner, Ryan
ABSTRACT: One of the primary eviction prevention measures jurisdictions across the country have taken is to expand access to free legal counsel for low-income tenants facing eviction. In 2017, New York City became the first jurisdiction to enact universal access to counsel (UAC), guaranteeing free legal representation to all low-income tenants facing eviction in the city's housing courts, and other cities are also starting to channel significant resources into programs designed to increase representation in eviction proceedings. Proponents argue that access to counsel will reduce the incidence of evictions and decrease levels of homelessness. Research, however, has yet to evaluate these claims rigorously. We aim to address this gap by examining the effectiveness of legal representation in preventing evictions. Specifically, we study the early implementation of UAC in New York City and use its sequential rollout across ZIP Codes to study impacts on both individual case outcomes and broader eviction patterns. We find relative increases in legal representation for treated ZIP Codes after the adoption of UAC. We also see small relative (and absolute) reductions in the share of filings resulting in executed warrants after UAC was implemented in the earliest ZIP Codes.